TAX DATA MIGRATION THROUGH CORE TAX ADMINISTRATION SYSTEM : A NETNOGRAPHIC STUDY OF DIGITAL TAX CUMMUNITY DISCOURSE - Sandy Novianto Sandy; Fidiana Fidiana (RADJA PUBLIKA, 2026)
The digital transformation of tax administration has become one of the most significant public sector reforms undertaken by governments worldwide. Indonesia has accelerated this transformation through the implementation of the Core Tax Administration System (Coretax), an integrated platform intended to replace fragmented digital tax applications and establish a unified tax administration database. Despite its strategic importance, the early implementation of Coretax generated considerable discussion among taxpayers, tax consultants, and accounting professionals regarding technical reliability, usability, and adaptation to the new system. This study investigates how digital tax communities socially construct meanings and responses toward the migration to Coretax during its initial implementation phase This research adopts a qualitative approach using netnography. Data were collected through passive observation of publicly accessible discussions within Telegram tax communities, Twitter/X conversations, and online tax forums between January and August 2025. Qualitative data analysis was conducted using open coding, axial coding, and selective coding to identify dominant discourse themes and explain the socio-technical dynamics underlying user experiences The findings demonstrate that Coretax implementation represents a socio-technical transformation rather than merely a technological migration. Five dominant themes emerged from the digital discourse: system errors, user interface confusion, emotional resistance, collaborative adaptation, and system stabilization. Users experienced three consecutive migration phases characterized by initial confusion, resistance triggered by technical instability, and gradual acceptance following continuous system improvements. The study concludes that successful digital tax transformation depends not only on technological capability but also on effective communication, digital literacy, institutional responsiveness, and public trust. These findings contribute to the growing literature on digital taxation by highlighting the importance of social construction processes and online communities in shaping public sector technology adoption.